1990
DOI: 10.1038/bjc.1990.305
|View full text |Cite
|
Sign up to set email alerts
|

Potential usefulness of quinine to circumvent the anthracycline resistance in clinical practice

Abstract: Quinine, the widely used antimalaria agent, was found to increase the cytotoxicity of epideoxorubicin (epiDXR) in resistant DHD/K12 rat colon cancer cells in vitro. Quinine appeared as slightly less effective than quinidine or verapamil for anthracycline potentiation but its weaker cardiotoxicity could counterbalance this disadvantage in vivo. Serum from six patients treated by conventional doses of quinine (25-30 mg kg-1 day-1) was demonstrated to enhance the accumulation of epiDXR in DHD/K12 cells as judged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 13 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…17,18 We have previously demonstrated that quinine was a good candidate for evaluating the clinical interest of MDR-reversing agents. 19 Serum from patients receiving conventional doses of quinine by intravenous infusion reverses the MDR phenotype of various tumor cell lines. 19,20 Quinine is safe when combined with mitoxantrone and cytarabine for treating acute leukemia patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 We have previously demonstrated that quinine was a good candidate for evaluating the clinical interest of MDR-reversing agents. 19 Serum from patients receiving conventional doses of quinine by intravenous infusion reverses the MDR phenotype of various tumor cell lines. 19,20 Quinine is safe when combined with mitoxantrone and cytarabine for treating acute leukemia patients.…”
Section: Introductionmentioning
confidence: 99%
“…19 Serum from patients receiving conventional doses of quinine by intravenous infusion reverses the MDR phenotype of various tumor cell lines. 19,20 Quinine is safe when combined with mitoxantrone and cytarabine for treating acute leukemia patients. 21,22 This compound does not significantly improve the response rate of refractory and relapsed acute myelogenous leukemias 22 but increases the response of P-glycoprotein-expressing myelodysplastic syndromes to a mitoxantrone-Ara-C combination.…”
Section: Introductionmentioning
confidence: 99%
“…These agents include verapamil, 8) nifedipine, 9) quinidine, 10) quinine, 11) cyclosporin, 12) tamoxifen, 13) and toremifene. 14) Among these P-glycoprotein inhibitors of the first generation, verapamil and cyclosporin were the most active and most often tested in clinical studies.…”
mentioning
confidence: 99%
“…17 The clinical use of most of these drugs is precluded by serum protein binding or clinical toxicity. 18 We observed that serum from patients receiving conventional doses of quinine by intravenous infusion reversed the MDR phenotype of rat colon cancer 19 and human leukemic cells. 20 Based on this observation, quinine appeared as a good candidate for evaluating the clinical interest of MDR reversing agents.…”
Section: Introductionmentioning
confidence: 90%
“…[17][18][19] A 12-h cinchonine infusion was required to reach an optimal MRA. After cinchonine infusion arrest, both drug serum level and MRA decreased rapidly, suggesting that cinchonine infusion might be maintained for at least 3 h after chemotherapeutic drug administration.…”
Section: Discussionmentioning
confidence: 99%